Is informal education the answer to increasing and widening participation in STEM education?. Issue 2 (28th February 2017) - Banerjee, Pallavi Amitava
Abstract : This paper summarises research findings from a longitudinal national evaluation of science, technology, engineering and mathematics (STEM) 'enrichment and enhancement activities'. The activities included science practical lessons, supported by ambassador visits, trips to laboratories, STEM centres and higher education institutions. The common theme for these activities was their aim to improve understanding and enjoyment of science in the short term and encourage STEM participation in the long term. The 2007 cohort across all state maintained secondary schools in England was followed up from the beginning of key stage 3 to the end of key stage 5 making use of school and pupil level datasets from the national pupil database. The study investigated whether engaging in these STEM programmes, run for 11–16 year olds, in secondary school is likely to affect subject choices during post‐compulsory education? Do young people sparsely represented in STEM courses such as those from a lower socio‐economic class and black ethnic minority engage better with STEM subjects because of actively participating in these activities? A direct noticeable impact of these activities was not seen on STEM take‐up. The analysis presented here concludes there is no evidence to suggest continued engagement in these activities is manifested in terms of increasing or widening STEM participation.